Occurrence and Seasonal Fluctuation of some Lepidopterous Defoliators of Sal (Shorea robusta) in Godapiasal, Midnapore, West Bengal, India - Khatua, A. K. (Indian Forester, 1997)
Studies on occurrence and sea sonal fluctuation of six important lepidopterous defoliators of Sal viz., Chatra grisea, Trabala vishnou, Lymantria ampla, Selepa celtis, Stictoptera cuculloides and Tetridia caletoralis in Godapiasal forest area of Midnapore, reveal their maximum availability during October, January, July, April, May and April respectively. Seasonal indices of the respective species are computed accordingly. Nature of damage by the respective caterpillars and their natural enemies are also studied. Defoliation in this dry deciduous forest is maximum during pre-monsoon period by T. caletoralis, during monsoon by L. ampla, during post-monsoon period by C. grisea and during winter period by T. vishnou.